2010
DOI: 10.1002/syn.20865
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter inhibition is necessary for cocaine‐induced increases in dendritic spine density in the nucleus accumbens

Abstract: Repeated exposure to cocaine produces changes in the nervous system that facilitate drug-seeking behaviors. These drug-seeking behaviors have been studied with animal models, such as cocaineinduced locomotor sensitization. Cocaine is hypothesized to induce locomotor sensitization by neural changes, including an increase in the density of spines on the dendrites of neurons in the nucleus accumbens (NAC). However, how cocaine increases dendritic spine density in the NAC has been difficult to discern because coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…Although cocaine is able to inhibit the reuptake of DA, noradrenaline and serotonin, its powerful effect is believed to ensue from its actions on the dopamine transporter (DAT) in neuron terminals, causing an increase of the concentration and of the intensity of action of DA at the postsynaptic receptors ( Fig. 1) (Gowrishankar et al 2014;Martin et al 2011). A recent study developed by Northcutt and colleagues demonstrated that cocaine can interact with Toll-like receptor 4 (TLR4) on microglial cells, to initiate central innate immune signalling.…”
Section: Dopamine Toxicity Caused By Cocaine Addictionmentioning
confidence: 99%
“…Although cocaine is able to inhibit the reuptake of DA, noradrenaline and serotonin, its powerful effect is believed to ensue from its actions on the dopamine transporter (DAT) in neuron terminals, causing an increase of the concentration and of the intensity of action of DA at the postsynaptic receptors ( Fig. 1) (Gowrishankar et al 2014;Martin et al 2011). A recent study developed by Northcutt and colleagues demonstrated that cocaine can interact with Toll-like receptor 4 (TLR4) on microglial cells, to initiate central innate immune signalling.…”
Section: Dopamine Toxicity Caused By Cocaine Addictionmentioning
confidence: 99%
“…Self-administration paradigms were used to control for the contribution of contingency and route of administration on the effects of the DA system. A long-access (LgA) procedure was used in which cocaine levels were sustained for 6 h each day (Ahmed et al, 2003;Martin et al, 2011;Peraile et al, 2010). This was compared with an intermittent-access (IntA) self-administration procedure in which cocaine was available during a 6-h session but only during 5-min trials, which were separated by 25-min timeouts.…”
Section: Introductionmentioning
confidence: 99%
“…More recently it has been suggested that cocaineinduced dendritic spine changes are correlated with the presence of DAT, because mice lacking DAT did not show an increase in dendritic spine density in the NAcc [30]. In addition, the stereotypy induced by cocaine is also absent in this transgenic mouse [56].…”
Section: Discussionmentioning
confidence: 76%
“…In addition, mice lacking DAT generally failed to acquire and maintain cocaine selfadministration [29] compared to wild-type, SERT-/-mice. Therefore, DAT inhibition may play a role in mediating the long-lasting neural changes associated with drug addiction [30,31].…”
Section: Discussionmentioning
confidence: 99%